DEVELOPMENT OF MATHEMATICS E-MODULE TO IMPROVE STUDENT'S LEARNING ACHIEVEMENT (Study on Class XII Students of SMAN 1 Gumay Talang - Ety Ruspitah; Johanes Sapri (DIADIK, 2019)
This study aims to: (1) produce Mathematical E-Modules that are suitable for use in mathematics learning (2) describe the effectiveness of Mathematical E-Modules in improving student achievement. This research is an R&D research (Research and Development) with a 4-D model (Define, Design, Develop, Dessiminate).The research subjects consisted of teachers and students of Gumay Talang 1 High School. The instruments used were the e-module feasibility assessment questionnaire, student and teacher response questionnaire, and cognitive test questions. Data analysis used t tests. The results of the study show that: (1) The mathematical e-module developed is appropriate for improving student learning achievement. (2) The developed mathematical e-module is an effective teaching material to improve student achievement in class XII of SMAN 1 Gumay Talang